Etika dan Tanggung Jawab Penggunaan Teknologi dalam Katekese Digital - Margareta Vera Lema; Emmeria Tarihoran (International Forum of Researchers and Lecturers, 2024)
This article discusses ethics and responsibility in the use of technology in the digital age, with a focus on the context of digital catechesis in Catholicism. Digital catechesis comes as an effort to convey knowledge and values of the Catholic faith by utilizing digital technology. This article will discuss digital catechesis in the context of the digital age, focusing on its benefits and challenges. In the digital age, language etiquette becomes very important to build harmonious relationships and avoid conflict. Technology has brought great changes in various aspects of life, including in the field of faith education. This research uses a qualitative method with a literature study approach to analyze related literature. Digital catechesis is the use of technology in faith learning and enables the dissemination of religious values in a more understandable and relevant way. Digital media such as video, audio, and social media facilitate active interaction and participation in catechesis. However, digital media also brings negative impacts such as intellectual property rights violations and potential misuse of information. Therefore, it is necessary to understand and apply proper ethics in the use of technology and utilize digital media as a tool to direct and guide the current generation towards repentance and good spiritual growth. Thus, digital catechesis can strengthen faith and guide the current generation in good spiritual growth in the digital age